STUDI PERBANDINGAN POSITIVISM DAN POST-POSITIVISM, TEORI KRITIS DAN KONSTRUKTIVISME TERHADAP PERKEMBANGAN PENGETAHUAN DAN PENELITIAN - Ado, Yahya Raja; Lestari, Gunarti Dwi; Susilo, Heryanto (MOTORIC, 2025)
This article discusses four main paradigms in the philosophy of science: Positivism, Post-positivism, Critical Theory, and Constructivism. These paradigms play a significant role in shaping research methodologies and perspectives on knowledge. Positivism is rooted in the belief that truth can be attained through empirical observation and deductive logic, while post-positivism acknowledges the limitations of objectivity and the importance of social context in knowledge formation. Critical Theory focuses on emancipating individuals from oppressive power structures, whereas Constructivism emphasizes the role of individuals in constructing reality. This article aims to provide a comprehensive analysis of the concepts, comparisons, and applications of these paradigms in scientific research. Keywords: Positivism, Post-positivism, Critical Theory, Constructivism, Philosophy of Science